Answer:
(t^2 -4) (t^2 +4)
(t-2)(t+2)(t^2+4)
Step-by-step explanation:
t^4 - 16
We can write this as the difference of squares
We know the dfference of squares is
(a^2 - b^2) = (a-b) (a+b)
( t^2 ^2 - 4^2) = (t^2 -4) (t^2 +4)
We can write t^2 -4 as the difference of squares
t^2 -4 = t^2 -2^2 = (t-2)(t+2)
Replacing this in
( t^2 ^2 - 4^2) = (t^2 -4) (t^2 +4) = (t-2)(t+2)(t^2+4)
x + y = 3
- x - x
y = -x + 3
y - y₁ = m(x - x₁)
y - (-1) = -1[x - (-1)]
y + 1 = -1(x + 1)
y + 1 = -1(x) - 1(1)
y + 1 = -x - 1
- 1 - 1
y = -x - 2
The answer is B.
Answer:
Step-by-step explanation:
2.5 = 5 * .5
1 = 1
70 = 2 * 5 * 7
LCM = 2 * 5 * 7
If you include the 1/2, you will reduce the LCM to 35, but 70 will be left out of the LCM.
The y intercept is 4, and the x intercept is 0.
Answer:
The answer is D,
a(n) = 4/5 + 1/6(n- 1)
just took the test :)
Step-by-step explanation: